AKTIVITAS INHIBITOR TIROSINASE PADA EKSTRAK ALGA COKELAT SARGASSUM SP. AGARDH ASAL PESISIR LHOK BUBON, KABUPATEN ACEH BARAT - Muhammad Gazali (Universitas Teuku Umar, 2018)
Seaweeds are marine macro algae that can be found attach to the bottom shallow coastal waters with subsrate as attached media. There are three major groups of seaweeds namely brown algae (Phaeophyta), red (Rhodophyta) and green (Chlorophyta). Sargassum sp is one of brown algae which mostly found in the Lhok Bubon Coastal West of Aceh. Recently, exploration of marine macroalgae as bioactive sources was investigated. Seaweed contains bioactive compound which can serve as a defense from ultraviolet radiation that caused hyperpigmentation effect. The aiming of this study is to analyse the tyrosinase inhibitory activity of Sargassum sp extract from Lhok Bubon Coastal Area, West of Aceh. The results shown that the methanol extract of Sargassum sp possess phytochemical properties such as fenol, alkaloid and triterpenoid. Tyrosinase inhibitory activity of Sargassum sp methanol extract is the best extract which can be inhibit monophenolase with IC50 : 1111.49 µg/ml and IC50 = 1582.31 µg/ml in diphenolase pathway with kojic acid as positive control. Moreover, etyl asetate and n-hexane extract have no activity of tyrosinase inhibitor. Therefore, new finding of tyrosinase inhibitor agent from marine macroalgae Sargassum sp give the fruitfull information for cosmeceutical industry.Keywords : Lhok Bubon, Brown Algae, Sargassum sp, Tyrosinase Inhibitor